A populaç\~ao em situaç\~ao de rua nos números do Cadastro Único - Marco Antonio Carvalho Natalino (Instituto de Pesquisa Econômica Aplicada (IPEA), 2024)
– The article describes and analyses data on the homeless population that are available in the Cadastro Único. The aim is to present some input to the betterment of public policies, offering a diagnostic of the current situation in Brazil. The article also presents a method for the compilation, cleaning and analysis of the single registry. A series of factors made that more and more citizens became homeless over the last decade. With the covid-19 pandemic the situation worsened. In July 25th 2023 The Supreme Court of Brazil published a decision that, among other things, mandates the federal executive to make an action plan, and that such action must include a diagnostic of the situation. The main reasons for homelessness are economic conditions, family conflicts and health issues. Economic reasons are associated with shorter duration homelessness. The opposite is true for the other two main reasons. Migrations, places of sleep, family bonds, community participation and general characteristics of the public such as race/'color', sex, age and disabilities are also discussed. Gender inequality in childcare is also present in this group: women are 11.6% of the adult homeless and 35% of those that responsible for the children in such conditions. The article also discusses access to documents, health services, social services, the Bolsa Família social benefit, schooling, work and income generating activities. Among the adults, 24% do not have work documentation (carteira de trabalho) and 29% do not have electoral documentation (título de eleitor). Among all registered homeless (which means they have at least a civil registry) 24% have no certificate of birth. Only 58% of children between the ages of 7 and 15 are enrolled in school. Only 1% of adults have a formal job, but 69% are envolved in at least one income generating activity.
Keywords: D60; I39; J19; Y10; 330; homelessness; CadÚnico; social indicators; social vulnerability; poverty